Kajian Program Pengembangan Dan Pemberdayaan Masyarakat (PPM) Di PT Batu Mulyo Berjaya Kec. Kesugihan, Kab. Cilacap, Prov. Jawa Tengah - Guntil Frans, Susana; Purnomo, Hendro; Ali Mohamad, Mustapa (Jurnal of Mining Insight, 2023)
PT. Batu Mulyo Berjaya is one of the companies with IUP 543.32/3666 of 2020 which is engaged in mining and crushing andesite stones. Community Development and Empowerment Program at PT. Batu Mulyo Berjaya must focus on vulnerable or underpowered community groups by carrying out community development activities aimed at forming an independent society. The purpose of this study is (1) to find out the community development and empowerment programs that have been carried out by PT. Batu Mulyo Berjaya in Pesanggrahan village, (2) knowing the benefits felt by residents in Pesanggrahan village to community development and empowerment programs, (3) knowing the community development and empowerment programs that have not been carried out by PT. Batu Mulyo Berjaya to the community in Pesanggrahan village. The method of determining the sample was simple random sampling with a sample of 10 respondents. The results of the study show that the program implemented has referred to the Ministry of Energy and Mineral Resources 1824 K/30/MEM of 2018 concerning Guidelines for the Implementation of Community Development and Empowerment, where in the regulation there are 8 (eight) program areas, namely, education, health, increasing real income, economic independence, socio-culture, environmental management between the community and companies, the formation and strengthening of institutional organizations, and the development of supporting infrastructure for the program community development and empowerment. Furthermore, the public's perception of the community development and empowerment program carried out by PT. Batu Mulyo Jaya, from the results of the research, it can be seen from the community's satisfaction with the PPM program, and public knowledge about the PPM program implemented by the company.